Mechanistic modeling and applications for CHO cell culture development and production. (December 2018) - Sha, Sha; Huang, Zhuangrong; Wang, Zhao; Yoon, Seongkyu
Highlights: Mechanistic models describe cellular metabolism and behavior in response to cell culture. Stoichiometric and kinetic models are widely used in mechanistic models. Mechanistic models are applied in process understanding, process optimization and control. Abstract : Chinese hamster ovary (CHO) cell cultures are widely used to produce biologics in the biopharmaceutical industry. The biopharmaceutical industry requires to improve the efficiency of process development as a response to the increasing market competition. The traditional approaches to optimize cell culture are typically empirically-based and generally time-consuming. The use of mechanistic models can be beneficial to these industrially relevant exercises and improve the efficiency of process development. This review introduces stoichiometric and kinetic models, the two commonly used mathematical approaches to describe cell system, and discusses the challenges associated such as parameterization and generalizability with respect to model applications. Examples of applying mechanistic models across the stages of process understanding, optimization and control are reviewed.